Study on the development of a quaternary layer of B4C-TiB2-Al3Ti-Al in AA7050 / B4C Ex-Situ composite and influence of heat treatment on mechanical and wear properties / Arvind Kumar and Ram Naresh Rai - Kumar*,, Arvind; Rai, Ram Naresh (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2020)
In the current investigation, AA7050-B4C composite developed through flux assisted (K2TiF6 flux) stir casting method. The FESEM microstructure studies confirm the uniform distribution of the reinforcements. The EDAX analysis confirms the formation of the intermetallic phase of TiB2 and Al3Ti across the interface of B4C particles and the aluminium matrix. The developed composite was heat treatment as per T-6 specifications, and a comparative study has been done on microstructures, mechanical properties and wear properties for ascast composite(ACC) and Heat-treated composite (HTC). The effect of heat treatment on the microstructure and bond mechanism shows that the B4C particles are fairly incorporated in the matrix. Ti decomposes and forms quaternary layers of B4C-TiB2-Al3Ti-Al across B4C particles. These layers not only prevent the decomposition of B4C particles into the matrix, also acts as the effective load transfer layers. Consequently, there is an enhancement in tensile strength by 16.4%, hardness by 15.9%, compressive strength by 14.8%, and impact strength by 10.9%. This may be due to the interface strengthening and precipitation hardening mechanism. There is a significant reduction in wear rate and coefficient of friction after heat treatment; this may be due to the improvement in hardness and compressive strength of the composite.